9th International Workshop on Spoken Dialogue System Technology
XVI, 421 p. 87 illus., 59 illus. in color.
Keywords: This book presents the outcomes of the 9th International Workshop on Spoken Dialogue Systems (IWSDS), “Towards creating more human-like conversational agent technologies”. It compiles and provides a synopsis of current global research to push forward the state of the art in dialogue technologies, including advances in the context of the classical problems of language understanding, dialogue management and language generation, as well as cognitive topics related to the human nature of conversational phenomena, such as humor, empathy and social context understanding and awareness.